Challenges Associated with the Development of Oil and Gas Sector in Uganda - Lyakurwa, William (The African Economic Research Consortium, 2012)
The subject matter of challenges associated with the development of the oil sector is commonly acknowledged as being inadequate. The danger is that many African governments often repeat past mistakes by assuming that the oil would be permanent, therefore making unsustainable long-term spending commitments. The production of oil poses a number of challenges, including the impact of the potential scale of revenues on consumption patterns, inflation and demand for certain goods and services, and the impact of price and production volume volatility on public spending and debt. The revenue generated from oil raises national income, hence it is optimal to increase consumption and investment. However, many of the consumption and investment goods desired by a richer population are of a non-traded nature. Supply capacities in non-traded goods industries can only be increased gradually, as this requires investment in new plant and equipment and the employment, and training where necessary, of more workers. Hence, the increases in demand for non-traded goods will create excess demand relative to supply and drive up the prices of these goods, causing inflation.